Long non-coding RNAs in response to Ebola virus vaccine-induced immunity - Mamede, Izabela; Luschër-Dias, Thomaz; Moscardini, Isabelle Franco; Gonzales-Dias, Patrícia; Marinho, Bárbara; Marcon, Fernando; Dominguez Crespo Hirata, Thiago; Eichberg, Michael; Medaglini, Donata; Harandi, Ali M.; Siegrist, Claire-Anne; Ottenhoff, Tom H. M.; et al. (Frontiers in Immunology, 2026)
Long noncoding RNAs (lncRNAs) have emerged as critical regulators of gene expression, yet their role in shaping human responses to vaccination remains largely uncharacterized. Here, we analyzed RNA-sequencing data from three independent human cohorts vaccinated with the rVSVΔG-ZEBOV-GP Ebola vaccine to profile lncRNA expression dynamics. Using differential expression analysis and correlation meta-analysis across cohorts, we identified an expression signature with several lncRNAs, including LEF1-AS1 and DOCK8-AS1, that exhibit conserved transcriptional activation following vaccination. Correlation of lncRNA expression with gene targets and IgG titers revealed putative roles for lncRNAs in regulating and/or participate in both innate immune responses and adaptive antibody production. Functional enrichment of lncRNA co-expressed protein-coding genes highlighted involvement in T-cell differentiation, interferon signaling, and leukocyte activation. Integrating global run-on sequencing data and comparative transcriptomic analysis across other vaccine studies suggests that LEF1-AS1 modulation is distinctively associated with Ebola vaccination. Our findings demonstrate that lncRNAs are potential integral components of the human vaccine response and provide a foundation for future mechanistic studies targeting noncoding RNA regulation of immunity.